KAJIAN HIDROGRAF BANJIR DAERAH ALIRAN SUNGAI TANJUNG PARAK PADA PEMBANGUNAN EMBUNG PULAU TIGA - Mashuri; Miskar Maini; Aulia Hidayat Burhamidar (Jurnal Infrastruktur, 2022)
The Purpose of construction the reservoir to control flood and rainwater reservoir . In Rainy Season, Pulau Tiga Village always flood due to overflow of the Tanjung Parak river and at dry season, people have difficulty getting raw water. For this reason, it is necessary to build reservoir as an effort to control flooding and water absorption especially in rainy season and as rainwater reservoir to demand raw water people.The reservoir planning requires the study of the flood hydrograph in the Tanjung Parak Watershed using the synthetic unit hydrograph method. The SCS, Nakayasu, and ITB-1 method were used in flood hydrograph analysis. The performance of all HSS modeling are very good and qualified based on volume control value/ direct runoff (dro) is close to 1 where the HSS SCS method is 0,99891 with volume 749,18 m3, the nakayasu HSS method is 1,07161 with volume 803,71 m3 and the HSS ITB-1 method is 1,00821 with volume 756,16 m3. The peak discharge for the 25-year return period due to hyetograph 6 hours with the SCS Method 12.70 m3/ s with volume 39447,80 m3, the Nakayasu Method 13,14 m3/ s with volume 43758,16 m3 and the ITB-1 Method 12,76 m3/ s with 39658,17 m3. The value of HSS SCS method is considered to represent flood hydrograph in Tanjung Parak river because volume/ dro value is closer to 1 than HSS ITB-1 and HSS Nakayasu methods so peak discharge and hydrograph volume will be basic for calculations in planning reservoir dimensions and other.